PERBEDAAN RETURN-SESUAIAN RISIKO ANTARA VALUE STOCK DAN GROWTH STOCK DI BURSA EFEK INDONESIA - Gunawan, Kadek Hendra; Sujana, I Ketut; Suputra, I.D.G Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
The purpose of this study is to verify the differences risk-adjusted return between value stocks and growth stocks at Indonesia Stock Exchange. The population in this study are all companies listed on the ISE period 2011 to 2015. The sample of the selection is using purposive sampling technique and acquired from 15 companies, consisting of 9 value stocks and 6 growth stocks. The formation of the portfolio based on price to book value ratio and price to earnings ratio. Data analysis techniques which are being used are Mann Whiteney Test and Independent Sample t-Test. The analysis show that the risk-adjusted return on value stocks is higher than risk-adjusted return on growth stocks. Based on these results, it can be concluded that there is a value premium at the Indonesia Stock Exchange and this indicate that the Indonesian Stock Exchange is classified as a weak form of the efficient market.
Keywords: value stock, growth stock, risk-adjusted return, price to book value, price to earning